DIVERSIFIKASI BUAH BLIGO (BENINCASA HISPIDA) PADA MASYARAKAT DI DESA KUTUH, KECAMATAN KUTA SELATAN, BADUNG - Mutria Farhaeni; Luh Kadek Budi Martini; Ni Putu Widiastuti; Ni Komang Prasiani (Universitas Mataram, 2023)
In general, South Kuta District has agricultural land that is quite extensive and has the potential to be utilized as business development, in the field of dry land agriculture and processed agricultural products. One of the agricultural products in Kutuh Village is Bligo fruit. Bligo fruit is a vine that is grown because the fruit is edible and is considered a vegetable. Bligo fruit or often referred to as kundur fruit (Benincasa hispida Thunb Cogn) this fruit is often consumed by people in Kutuh Village processed as vegetables for their own consumption, this fruit is widely available in Kutuh Village. Therefore, this service activity aims to increase knowledge and skills in processing bligo fruit-based products. As well as to initiate and motivate the emergence of business ideas based on processed bligo fruit. Community service activities are carried out in Kutuh Village, South Kuta District, Badung. This activity was carried out on August 8 2023. A total of 24 (twenty four) participants attended this activity, each consisting of 16 (sixteen) members from the PKK of Kutuh Village, 4 (four) people from the KWT of Kutuh Village and 4 (four) people from the village apparatus. The method used to solve the problem is to carry out socialization activities, training and mentoring for the diversification of bligo fruit-based products, namely pie, sweets and chips as well as product packaging. The results of this dedication are that (1) bligo fruit can be processed into various products such as pies, sweets, and chips. (3) packaging and labeling. Participants stated that this activity was by the needs of partners, namely being able to empower the community, especially village women, to be able to motivate and encourage the entrepreneurial spirit of program participants.